DYSTOCIA DUE TO BILATERAL HOCK FLEXION IN A JENNY (EQUUS ASINUS) - SACHAN, V; KUMAR2, B; SAXENA, A; CHAUDHARY, M K (The Indian Journal of Animal Reproduction, 2022)
A case of fetal dystocia due to bilateral hock flexion in a jenny and the successful per-vaginum delivery of fetus is reported through partial fetotomy using double barrel Thygesen fetotome.